2015
DOI: 10.1007/s12080-015-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Population spread in patchy landscapes under a strong Allee effect

Abstract: Many species of invasive insects establish and spread in regions around the world, causing enormous economical and environmental damage, in particular in forests. Some of these insects are subject to an Allee effect whereby the population must surpass a certain threshold in order to establish. Recent studies have examined the possibility of exploiting an Allee effect to improve existing control strategies. Forests and most other ecosystems show natural spatial variation, and human activities frequently increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This is in accordance with the study by Musgrave et al . (), who have shown that the percentage of hostile patches at which populations collapse can depend on individuals’ movement behaviour, as introducing hostile patches can increase spread rates if individuals move fast enough.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the study by Musgrave et al . (), who have shown that the percentage of hostile patches at which populations collapse can depend on individuals’ movement behaviour, as introducing hostile patches can increase spread rates if individuals move fast enough.…”
Section: Discussionmentioning
confidence: 99%
“…Positive density dependence (Allee effects) generally leads to more restrictive conditions for invasion (Dewhirst and Lutscher , Musgrave et al. ). Density‐dependent movement can also affect rates of range expansion (Altwegg et al.…”
Section: Predicting Range Expansion In Heterogeneous Landscapesmentioning
confidence: 99%
“…Our model did not include an Allee effect, yet Allee effects play a role in many invasion processes. Even in a homogeneous landscape, there is no simple speed formula when an Allee effect is present, but two recent numerical and semi-analytical studies explored the impacts of landscape heterogeneity and Allee effect on invasion speeds Lutscher 2015, Musgrave et al 2015). Equally important, our model did not include an increased mortality risk in bad patches for the dispersing individuals (e.g., due to energy requirements or predation).…”
Section: Combined Behaviormentioning
confidence: 99%